Net Neutrality and Its Implications to Online Learning - Yamagata-Lynch, Lisa; Despande, Deepa; Do, Jaewoo; Garty, Erin; Mastrogiovanni, Jason; Teague, Stephanie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
In this article, we studied net neutrality as a complex sociocultural phenomenon that can affect the works of distance education scholars and online learners. We decided to take part in this research because many distance education scholars and learners take net neutrality for granted. We engaged in a qualitative investigation of US public documents and explored the effects of net neutrality and public digital access, which can influence learner engagement with online educational materials. We focused on identifying tensions in the discourse about net neutrality, especially surrounding the Federal Communication Commission’s (FCC) 2015 Open Internet Order. Our research question was: How do the complexities involved in the net neutrality debate in the United States affect public access to online information and services, and what implications does this hold for online learning? We relied on activity systems as an analytical framework for making sense of net neutrality.